(3EbJUGO GdeDSSI (B:s (3CgejI GdJfXje OjfGejcjI GdgjGcd (B/s - (3YQHGLj, GSeGYjds ([(3Ohf ecGf(B]: s)
(3jVe GdeDSSI hGdfXQjI GdYGeI, GdeHGOF GdYGeI GdJfXjejI hGdEOGQjI, GdeDSSI heMjWgG, GdJShjb, GdeNRhfGJ, GdJMdjd GdeGdj, GSJbdGdjI GdeDSSGJ, eLehYI eSGFd hJeGQjfGJ ddeQGLYI(B.s
(3HjHdjhZQGajG(B: (3U U(B.349-356s
Keywords: (3GdGbJUGOs; (3GdeDSSGJ GdJLGQjIs